Usability of Learning Media for Student Worksheets in the Aquatic Biology Course Based on a Mollusca Inventory at Sindangkerta Beach, Tasikmalaya - Ulfah Fauziyah; R. Ading Pramadi (International Journal of Learning Media on Natural Science (IJLENS), 2025)
The limited availability of Student Worksheets (LKM) in the Aquatic Biology course makes learning feel less effective by students because there are no worksheets to support this, resulting in a lack of motivation and interest in learning. This research aims to produce an Aquatic Biology Student Worksheet which was developed based on the Mollusca Inventory at Sindangkerta Beach, Tasikmalaya. The research was carried out using the R&D (Research and Development) method with a 3D model (define, design and development). The subjects in this research were 15 sixth semester students of the Biology Education Study Program at UIN Sunan Gunung Djati Bandung. The results of this research are in the form of a description of the development stages (define, design and development) of LKM products, the results of data analysis on validation aspects by material experts and media experts which were declared valid with an average percentage score of 83.79%, the student readability aspect is included in the category easy to understand (91.2%), and student responses were in the very positive category (88%). Based on the research conducted, it can be concluded that LKM based on the Mollusca inventory at Sindangkerta Beach, Tasikmalaya, is suitable for use as a learning medium in Aquatic Biology courses.